Case Report: Deutetrabenazine as an Adjunctive Treatment for Stuttering - Ha, Catherine A.; Maguire, Gerald A. (Frontiers in Psychiatry, 2021)
Childhood-Onset Fluency Disorder (Stuttering) is a neurodevelopmental disorder in which disturbances occur in the normal fluency and time patterning of speech. While the dopamine system has been well-described in its neurophysiology, there currently is no FDA-approved treatment for stuttering. Second-generation antipsychotics, which have been effective in the treatment of schizophrenia and bipolar disorder, act as dopamine D-2 receptor antagonists at the postsynaptic neuron and have been shown to reduce the symptoms of stuttering. However, the D-2 receptor antagonist and partial agonist agents carry the potential for metabolic side effects and can potentially lead to movement disorders. Deutetrabenazine, a VMAT-2 inhibitor indicated to treat hyperkinetic movement disorders, is a potential candidate in the treatment of stuttering, based on its mechanism of action in decreasing dopamine activity while not carrying the risk of metabolic adverse events.